INTERNATIONAL AND NATIONAL LEGAL MECHANISMS OF JUDICIAL LIABILITY IN THE CONDITIONS OF ECONOMIC GLOBALISATION OF MODERN SOCIETY - Konul Akhundova (Baltic Journal of Economic Studies)
The subject matter of the study is the conceptual, theoretical, empirical, methodological and applied foundations of international and national legal mechanisms of judicial liability in the context of economic globalisation of modern society. Methodology. The present study employed a combination of general scientific and special legal methodologies. Through meticulous analysis, the quantitative and qualitative characteristics of the economic and legal essence of an independent and impartial judiciary as the nation's sole arbiter of justice were systematically delineated. The synthesis yielded a comprehensive overview of the legal framework governing the judicial accountability of judges across diverse legal systems, with particular consideration for each system's economic level of development. The employment of a comparative legal methodology has facilitated the identification of both common and distinctive characteristics in both international and national legislation. This is a scientific development that is indicative of the legal mechanism for holding judges to disciplinary liability. The formal-legal method established the foundations for formulating conclusions regarding the effectiveness of existing national legal regimes for holding judges accountable. The purpose of the present article is to determine the specific features of international and national legal mechanisms of judicial liability in the context of economic globalisation in modern societies. The results of the study show that the existing international legal mechanism of judicial liability developed by international institutions is quite effective and promising for implementation within the framework of national legal regimes, and the national mechanism of judicial liability needs to be improved both in terms of procedure and means of its implementation in connection with the economic development of society. Conclusion. The establishment of functional indicators of the judiciary has been undertaken, which are convergent in combination with economic indicators of the population's well-being, conditions for opening one's own business, ensuring financial and banking stability, GDP growth, the level of development of relevant sectors of industry and the economic sphere as a whole, etc. Among the indicators that reproduce the productivity of all three branches of government, the following are highlighted: the government efficiency index - the executive branch, the legislation quality index - the legislative branch, the rule of law index - the judiciary. A direct dependence of the economic development and rule of law indices has been revealed, since under the condition of ensuring the latter, there is a guarantee of the harmonious existence of all sectors of society, and conditions are created to prevent the emergence of existential threats to the national interests of the state, including the provision of human rights and freedoms. The mechanism for bringing judges to disciplinary responsibility has been established in accordance with international standards, including 1) a special procedure for bringing judges to disciplinary responsibility, which is defined by law; 2) the formation of an independent body that should consider such cases; 3) ensuring the right of a judge to participate in such procedure directly or through a representative, to exercise his right of defence and to express his opinion; 4) the right to appeal against the decision taken on the basis of the results of this procedure; 5) the exhaustiveness of the sanctions that can be applied and their proportionality. Within the framework of the national legal systems of the countries under consideration, the features of holding judges accountable in relation to their professional activities and for offences committed outside them are determined, which mediate the implementation of the content of the immunity and immunity of such officials. The procedure for holding judges criminally and disciplinarily liable is highlighted separately, and the reasons, grounds, procedure and subjects of the above-mentioned proceedings are determined, which indicates the special status of bodies that ensure the achievement of a social compromise in the influence of society on the judiciary, in combination with the construction of ensuring the immunity of judges.